Komunikasi Profetik dalam Pedoman Hidup Islami Warga Muhammadiyah (PHIWM): Integrasi Nilai Transendensi dan Praktik Sosial - Marlida, Siti; Widiyanto, Kelik Nursetiyo; Syahidah, Shopiah; Syah, Habib Fauzan (FASTABIQ: JURNAL STUDI ISLAM, 2025)
Communication theories, characterized by their humanistic and anthropocentric nature, are deemed insufficient in addressing communication needs grounded in transcendental values. Therefore, this study examines prophetic communication as an alternative paradigm in communication science, focusing on its implementation in the Islamic Life Guidance for Muhammadiyah Members (Pedoman Hidup Islami Warga Muhammadiyah/PHIWM). The theoretical framework of this research is based on the concept of prophetic communication, which emphasizes the integration of insaniyah (human) and ilahiyah (divine) dimensions in the communication process. This theory is critically compared with secular and anthropocentric communication approaches. This study employs a qualitative approach with a literature review method. Data were collected through in-depth analysis of religious texts (particularly the Qur'an), PHIWM documents, and related literature on prophetic communication and Islamic communication. Thematic analysis was conducted to identify the principles of prophetic communication within PHIWM. The findings reveal that PHIWM adopts prophetic communication principles derived from the Qur'an, encompassing four forms of communication: (1) interpersonal (compassionate and honest), (2) business (just and anti-usury), (3) organizational (collaborative and responsible), and (4) group (dialogic and inclusive). Transcendental values serve as the foundation for all these communication practices. This study recommends developing a PHIWM-based prophetic communication model for broader contexts, including education and media. Further research is needed to explore the impact of prophetic communication on social harmony, as well as comparative studies with communication theories. Keywords: Prophetic Communication; Transcendence; Muhammadiyah; Qur'an